Emotion and International Business: Theorising Fear of Failure in the Internationalisation - Dong, Rebecca Kechen (Frontiers in Psychology, 2022)
TThe road to internationalisation is paved with risk, uncertainty, the possibility of failure, and the COVID 19 phenomenon. However, the process of internationalisation theory treats an individual decision-maker as a ‘black box’. Emotions are largely ignored by international business researchers. This study offers conceptual thoughts on the role of fear of failure in the process of internationalisation. It argues that managers experience this emotion in making internationalisation decisions for a firm, which is an area of study requiring further understanding. Following the content analysis method in the literature review and a theory-based adaptation approach to complete the conceptualisation, this paper joins the scholarly conversations on ‘connecting the process of internationalisation model to people’ and ‘emotion and internationalisation’. Focusing on fear of failure as a new perspective, this paper contributes to international business literature by suggesting new avenues in understanding decision-making about international activities by embracing psychological insights. It also contributes to international business practitioners by offering implications for understanding one’s emotional state and its effect on decision-making about internationalising ventures.